Recent advance in laser powder bed fusion of Ti–6Al–4V alloys: microstructure, mechanical properties and machinability - Chenbing Ni; Junjie Zhu; Baoguo Zhang; Kai An; Youqiang Wang; Dejian Liu; Wei Lu; Lida Zhu; Changfu Liu (Virtual and Physical Prototyping)
Laser powder bed fusion (LPBF) of titanium alloys has demonstrated significant potential in high-value-added fields such as aerospace and biomedical. However, the highly non-stationary thermal history and inherent limitations of the LPBF process lead to critical challenges associated with LPBF Ti–6Al–4V components. This severely constrains the application and advancement of LPBF Ti–6Al–4V alloys. This paper focuses on the recent research progress on microstructure, mechanical properties and post-machining performance of LPBF Ti–6Al–4V alloys. Firstly, the influence of key process parameters and laser scanning strategies on forming properties of LPBF Ti–6Al–4V alloys is systematically overviewed. Subsequently, influenced by highly localised heat flow input, extremely high cooling rate and steep temperature gradient, the formation of common defects, non-equilibrium metallurgical structures and mechanical properties, and tensile residual stresses in as-built LPBF parts are analysed in-depth. Finally, the comprehensive machining performance of SLMed Ti–6Al–4V alloys is emphasised in terms of cutting force, surface morphology and roughness, subsurface microstructure evolution, variation of residual stress, and features of tool wear.